The influence of fixation temperature in in vitro DNA analysis - Canhoto, I. (2018)
Introduction: Formalin-fixed and paraffin-embedded (FFPE) are important sources for molecular studies, namely to identify cancer related biomarkers. Nevertheless, the quality of FFPE-obtained DNA is lower than that of fresh/frozen tissues, since fixation induces several chemical modifications. The impact of tissue fixation duration, fixative type and pH on the integrity of FFPE-extracted DNA has been the subject of several studies. It’s well established that fixation using formalin for less than 72 hours allows extraction of high quality DNA. Although it is known that DNA stability is highly dependent on temperature, the influence of the fixation temperature on the quality of FFPE-extracted DNA is not understood. Objective: Evaluate the influence of the fixation temperature in the quality of FFPE-extracted DNA through a systematic literature review. Materials and methods: The search was performed in PubMed for studies published in English, up to December 2017. The included studies compared two or more fixation temperatures using formalin, to perform DNA analysis. Results: Seven studies met the defined criteria. All compared room temperature (RT) with 4 °C (5 studies), 0-4 °C (1 study) or 37 °C (1 study). DNA integrity was evaluated by agarose gel electrophoresis electrophoresis, PCR, multiplex ligation-dependent probe amplification (MLPA) and whole gene amplification (WGA). In 5 studies the best results were obtained for fixation at 4 °C (electrophoresis, PCR and WGA); whereas RT allowed the best results in 2 cases (PCR and MLPA), one of which demonstrated that fixation at 37 °C preserved DNA similarly to RT. Conclusions: DNA stability is highly temperature-dependent as DNAses are inhibited at low temperatures. Accordingly, it is not surprising that fixation at 4 °C allows the extraction of less degraded DNA in most studies. Nevertheless, RT seems to be also an acceptable temperature, as it allowed successful MLPA and PCR when using small DNA fragments. From these observations one may conclude that tissue fixation must be performed at 4 °C if the goal is to analyse high-molecular-weight DNA. As RT is the standard fixation temperature in diagnostic lab units, these conclusions may imply the adequate adjustments in order to prevent false conclusions from molecular analysis. Nevertheless, additional studies that analyse not only DNA integrity, but also DNA purity, yield and concentration should be done to determine the optimal fixation temperature to perform molecular analysis.